Modelling a hydropower plant with reservoir with the micropower optimisation model (HOMER). Issue 7 (9th August 2017) - Canales, Fausto A.; Beluco, Alexandre; Mendes, Carlos André B.
Abstract : Hydropower with water accumulation is an interesting option to consider in hybrid systems, because it helps dealing with the intermittence characteristics of renewable energy resources. The software HOMER (version Legacy) is extensively used in research works related to these systems, but it does not include a specific option for modelling hydro with reservoir. This paper describes a method for modelling a hydropower plant with reservoir with HOMER by adapting an existing procedure used for modelling pumped storage. An example with two scenarios in southern Brazil is presented for illustrating and validating the method explained in this paper. The results validate the method by showing a direct correspondence between an equivalent battery and the reservoir. The refill of the reservoir, its power output as a function of the flow rate and installed hydropower capacity are effectively simulated, indicating an adequate representation of a hydropower plant with reservoir is possible with HOMER.